PENGARUH MODEL PEMBELARAN PROJECT BASED LEARNING (PJBL) TERHADAP AKTIVITAS DAN HASIL BELAJAR IPA MATERI SIFAT-SIFAT CAHAYA - Kuswandi; Panji Maulana; Setiawan, Wawan Eka (Sebelas April Elementary Education, 2023)
This research is motivated by the low activity and learning outcomes of fourth grade students at SDN Sukaratu 1 in the science subject matter of the properties of light. One effort that can be done is to apply a project-based learning model so that students are able to work together in groups, express opinions and make questions independently. This study aims to improve the activities and learning outcomes of science class IV students with a project based learning model. The research method used is Classroom Action Research (CAR). The instruments used in this study were the Learning Implementation Plan (RPP), syllabus, student activity observation sheets and tests. The results showed that the project based learning model could improve student activities and learning outcomes. student learning activities at first at 44.4% then increased to 90.00%. And improve student learning outcomes because student learning outcomes increased from 50% to 90.00%.